The Significance of Blunt Thoracic Trauma-Related Bronchial Stenosis Development in Terms of Loss of Earning Capacity in the Profession: Case Report - Soğukpınar, Veysel Osman; Terece, Cem; İçmeli, Özlem Saniye; Gürpınar, Kağan (The Bulletin of Legal Medicine, 2024)
Determining the rate of loss of earning capacity (disability rate) in the profession is important all over the world. Because the proportional determination of the limitation in a person’s body creates certain rights for the person. Relevant legislation has been regulated in this regard, although it varies in each country. The regulation in force in our country on this subject is the Regulation on Determination of the Ratio of Loss of Working Power and Earning Power in the Profession, issued in 2008. In evaluating loss of earning capacity in the respiratory profession, the pertinent regulation is also considered. Respiratory diseases are classified as mild-medium-severe under this regulation. We presented a case in which pneumomediastinum and hemopneumothorax developed as a result of a tractor trailer passing over the rib cage and stenosis in the left main bronchus was detected during follow-up, discussing disability within the scope of the relevant regulation.
Keywords: Disability; Blunt Thoracic Trauma; Bronchial Stenosis